(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
Structure formation is a very important phenomena to follow the cosmological evolution of our universe. The role of ultra-light dark matter in this whole process is substantial. Keeping this point in view, one anticipates that the extremely light dilatons can be expected play it’s part in this crucial process. The detection of the light dilatons is however not very easy, their cosmological signal may be detected in large radio telescopes. Using radiometer equation we ealborate on the possibility of detecting dilaton signal coming from the dark matter halo of nearby galaxies. Our analysis shows that in some parameter range the possibility of their detection is non-negligible.